Analysis of the role of the pineapple agribusiness subsector in increasing people's income in Blitar district - Ida Rohmah Susiani (Digital Business: Tren Bisnis Masa Depan, 2023)
This research is descriptive in nature, namely providing an overview and analysis of the current condition of the company's environment both internal and external to the company. This company faces various problems that must be resolved where fast environmental changes require companies to be more responsive in developing products to deal with the increasingly rapid growth of the insurance industry. This study aims to determine the strengths, weaknesses, threats and opportunities owned and faced by PT. Asuransi Jiwasraya (Persero) Malang Regional Office and determine the right strategy for the company in an effort to develop its business and achieve company goals. So from this research it is hoped that the company can take the right strategic steps in the company's operational activities. The analytical tool used in this study consists of three stages, namely the input stage, matching stage, and decision stage. At the input stage the analysis tools used include Internal Factor Evaluation (IFE) analysis and External factor Evaluation (EFE) analysis. At the matching stage, analysis tools are used in the form of Treath-Opportunity-Weakness-Strength (TOWS) analysis and Internal External (IE) analysis and by using the Quantitative Strategic Planning Matrix (QSPM) at the decision stage, various alternative strategies are analyzed and one strategy is prioritized for implementation. Based on the results of environmental analysis and company position , the strategy chosen is the market penetration strategy. The functional strategy in the field of operations or production includes sales promotions, product presentations, and product outreach. In the field of finance, it covers cost effectiveness and efficiency, simplification of bookkeeping procedures, and the proper use of budgets. In the field of marketing includes market penetration, sales of products that provide large profits, as well as payment of commissions and marketers' rights. And in the field of human resources includes implementing training and providing knowledge about new products.